Tree-Canopy Management and Soil Quality Index of Hardwickia binata Roxb. based Agroforestry System in Bundelkhand, Central India - Prasad, Rajendra; Newaj, Ram; Singh, R.; Handa, A. K.; Saroj, N. K.; Shukla, Ashok; Singh, Prashant; Tripathi, V. D. (Indian Forester, 2019)
The present study was conducted in a well established 22-years old Hardwickia binata based agroforestry system, aiming to evaluate effect of tree-canopy management practices on soil quality and how soil quality indicators respond to pruning treatments. The trial consisted of four treatments of pruning viz., control (no pruning), 25, 50 and 75% pruning of canopy height. To develop soil quality index (SQI), representative soil samples were drawn from 0-30 cm depth from all plots and analysed for selected soil quality indicators. Increase in pruning intensity of H. binata has shown favourable effect on most of the studied indicators. Maximum SQI was observed in plots receiving 75% while minimum in 25% pruning. In comparison to baseline, the improvement in SQI was the minimum in 25% (17.82%) and maximum in 75% pruning (30.93%). The improvement in soil quality over control ranged from zero (25% pruning) to 15.56% (75% pruning). The computed value of SQI (0-1 scale) ranged from 0.434 to 0.514 and had sensitivity of 1.49, reflecting its sensitiveness to management of the tree canopy. The infiltration rate (water movement) and biological activity were identified as sensitive and critical indicators for soil quality. Among treatments, 50% pruning of tree-canopy seems to be more desirable and effective in improving soil health in Bundelkhand region of central India.